Optimization of processes for the timely issuance of financial reports and the decision-making process, ClassWallet, Inc. - Monasterio-Pérez, Johnny; Márquez, Santiago; Maldonado Oliveros, Mariana (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE:  To propose methodologies for optimizing administrative and accounting management for the timely issuance of financial reports at ClassWallet, Inc.MATERIAL AND METHOD:  The research was based on a documentary and field study type, with a projective scope. The data collection method used was the direct observation technique of the management and accounting processes and procedures and the application of a semi-structured interview with experts in the finance area holding key positions within the organization.RESULTS: The results demonstrate that the administrative and accounting processes, which are subject to ongoing review, are fundamental for generating monthly and annual financial reports. CONCLUSIONS: By using the objectives, and key results, methodologies, the entity significantly improved the efficiency levels of those processes aimed at generating financial information suitable for the timely decision-making process at ClassWallet, Inc.
Keywords: processes optimization; financial reports; timely financial information; decision-making.